Scratch programming playground : learn to program by making cool games - Sweigart, Al (No Starch Press, 2016)
Learning how to program shouldn't be dry and dreary. With help from this easy-to-understand guide, you'll make a game of it by using Scratch, the colorful drag-and-drop programming language. Get ready to destroy asteroids, shoot hoops, and slice and dice fruit! --